2003
DOI: 10.1007/s00221-003-1494-5
|View full text |Cite
|
Sign up to set email alerts
|

Abducens conditioning in in vitro turtle brain stem without cerebellum requires NMDA receptors and involves upregulation of GluR4-containing AMPA receptors

Abstract: Previous work showed that in vitro abducens eyeblink classical conditioning of turtle brain stem-cerebellum preparations involved NMDA-mediated mechanisms and redistribution of GluR4-containing AMPA receptors in the abducens motor nuclei. Since conditioning can be obtained in brain stem preparations without the cerebellum, we examined whether similar mechanisms were involved during conditioning of the brain stem alone. The results showed that conditioning could not be induced in the presence of the NMDA recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Here, excitation of all abducens motoneurons is mediated by a mixture of AMPA and NMDA receptors, compatible with the membraneous presence of both receptor molecules (Durand et al, 1987;Durand, 1991;Keifer and Clark, 2003). The absence of a residual NMDA component after blocking the AMPA component reported previously (Straka and Dieringer, 1993) is likely due to the lack of background resting activity from the vestibular sensory periphery in isolated frog brains.…”
Section: Organization Of Excitatory Inputs To Abducens Motoneuronssupporting
confidence: 74%
“…Here, excitation of all abducens motoneurons is mediated by a mixture of AMPA and NMDA receptors, compatible with the membraneous presence of both receptor molecules (Durand et al, 1987;Durand, 1991;Keifer and Clark, 2003). The absence of a residual NMDA component after blocking the AMPA component reported previously (Straka and Dieringer, 1993) is likely due to the lack of background resting activity from the vestibular sensory periphery in isolated frog brains.…”
Section: Organization Of Excitatory Inputs To Abducens Motoneuronssupporting
confidence: 74%
“…Previous studies have demonstrated enhanced synthesis of GluR4 protein and increased localization of GluR4 subunits at synaptic sites corresponding with acquisition and expression of abducens CRs, but not with pseudoconditioning or treatment with the NMDAR antagonist AP-5 which blocks CRs (Keifer, 2001;Keifer & Clark, 2003;Mokin & Keifer, 2004;. In the present study, we have extended these findings to show that the synaptic localization of GluR4-containing AMPARs parallels the expression of abducens CRs during extinction and reacquisition of conditioning.…”
Section: Synaptic Incorporation Of Glur4-containing Ampars During In supporting
confidence: 77%
“…In an in vitro model of eyeblink classical conditioning, evidence suggests that synaptic delivery of GluR4-containing AMPARs supports conditioning through NMDAR-mediated mechanisms and MAPK signal transduction (Keifer, 2001;Keifer & Clark, 2003;Mokin & Keifer, 2004;Keifer, Zheng, & Zhu, 2007). In this system, in place of using tone and airpuff stimuli as in behaving animals, weak electrical stimulation of the auditory nerve (the "tone" CS) is paired with strong stimulation of the trigeminal nerve (the "airpuff" US) and results in a neural correlate of conditioned eyeblink responses recorded from the abducens nerve which controls eyeblinks in this species (Keifer, 2003, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Our initial studies of conditioning used an isolated brain stemcerebellum preparation (Keifer et al, 1995). However, subsequent studies found that an isolated brain stem preparation alone without the cerebellum could acquire robust CRs, although these had a significantly shorter onset latency compared to intact preparations Keifer, 1997, 1999;Keifer and Clark, 2003). These findings are similar to those obtained from rabbits with cerebellar cortex lesions (Perrett et al, 1993).…”
Section: Introductionmentioning
confidence: 55%